Performance, Evaluation, and Enhancement of Hydrated Cement Treated Crushed Rock Base (HCTCRB) as a Road Base Material for Western Australian Roads - Jitsangiam, Peerapong; Nikraz, Hamid (PATREC, 2010)
Hydrated Cement Treated Crushed Rock Base (HCTCRB) is widely used as a base course material for Western Australian roads. HCTCRB has been designed and used based on an empirical approach and practical experience, respectively, but those are not capable of explaining behavior of HCTCRB. Presently, a mechanistic approach becomes more reliable in pavement design and analysis and behavior of pavements can be more understood. Consequently, characterization of HCTCRB following the mechanistic approach is necessary. This study aimed to analyze the results of laboratory testing so as to assess the mechanical characteristics of HCTCRB. Conventional triaxial tests and repeated load triaxial tests (RLT tests) were performed. Factors, which would affect the performance of HCTCRB such as hydration periods and the amount of water added, were also investigated.